2014
DOI: 10.1007/s10891-014-1071-8
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of Physicochemical Processes Occurring During Water Evaporation in the Surface Layer Pores of a Forest Combustible Material

Abstract: A numerical investigation of the physicochemical processes occurring during water evaporation from the pores of the surface layer of a forest combustible material has been carried out. The characteristic features of the suppression of the thermal decomposition reaction of a combustible material with water fi lling fullyits pores and formation of a water fi lm over its surface have been determined. The characteristic times of suppression of thermal decomposition reactions under various environmental conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Furthermore, there is a research direction in the literature devoted to the study of the pyrolysis process during liquid evaporation [129][130][131]. These developments contribute to a deeper understanding of the processes occurring directly during pyrolysis and its suppression.…”
Section: Forest Fuel Pyrolysismentioning
confidence: 99%
“…Furthermore, there is a research direction in the literature devoted to the study of the pyrolysis process during liquid evaporation [129][130][131]. These developments contribute to a deeper understanding of the processes occurring directly during pyrolysis and its suppression.…”
Section: Forest Fuel Pyrolysismentioning
confidence: 99%
“…This knowledge is important for development of an appropriate mathematical models and the new techniques of localization and suppression of forest fires. In particular, the experimental database can be applied for development of the models of the FCM fire extinction under different heat transfer conditions, like described in [5,6].…”
Section: Resultsmentioning
confidence: 99%
“…This is due to the fact that a water mass (fire-extinguishing liquid) usually covers a quite limited FCM surface area [3]. In addition, recent theoretical studies [5,6] have shown that when large water masses are locally discharged to a fire site, about 90-95% of the liquid is involved in firefighting inefficiently. In this case, almost entire volume of water passes through the flame combustion zone without evaporation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations